Juridical Review of Defamation in the Context of Domestic Violence (KDRT) Evidence Videos Uploaded on Social Media - Robiatul Adawiyah; Nynda Fatmawati O (Dinasti Research, 2025)
Social media currently plays a significant role in everyday life, facilitating the sharing of information, including sensitive issues such as Domestic Violence (DV). Uploading videos as evidence of DV is often used as an attempt to seek public support or demand justice. However, this practice poses legal risks, particularly related to defamation, especially if the identity of the affected party is revealed. In Indonesia, defamation is regulated under the Criminal Code (KUHP) and the Electronic Information and Transactions Law (ITE Law), particularly Article 27, paragraph (3), which is frequently applied in social media-related cases. The dilemma arises in balancing the victim's right to disclose their experience of violence with the perpetrator's right to protect their reputation. These cases highlight the challenges of law enforcement in the digital era, where victims often turn to social media due to a lack of trust in formal legal systems, while others may use the law to defend their reputation. Data from the Ministry of Communication and Information (Kominfo) and the National Commission on Violence Against Women (Komnas Perempuan) show an increase in such cases, indicating the need for legal revisions that are more just and responsive to technological advancements and social dynamics.